2005
DOI: 10.1152/ajpheart.00638.2005
|View full text |Cite
|
Sign up to set email alerts
|

Depressed cardiac myofilament function in human diabetes mellitus

Abstract: Diabetes mellitus is associated with a distinct cardiomyopathy. Whether cardiac myofilament function is altered in human diabetes mellitus is unknown. Myocardial biopsies were obtained from seven diabetic patients and five control, nondiabetic patients undergoing coronary artery bypass surgery. Myofilament function was assessed by determination of the developed force-Ca2+ concentration relation in skinned cardiac cells from flash-frozen human biopsies. Separate control experiments revealed that flash freezing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
67
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 39 publications
7
67
1
Order By: Relevance
“…These findings were confirmed by Sharma et al, who demonstrated a fivefold to sixfold increase in intramyocardial lipid levels in obese, or type 2 diabetic, patients suffering from non-ischemic heart failure that was associated with a transcriptional profile similar to that of the Zucker diabetic fatty rat (Sharma et al, 2004). Finally, myofilament function is depressed in skinned fibers as a result of decreased Ca 2+ sensitivity, suggesting that Ca 2+ handling may also be impaired in human diabetic cardiomyopathy (Regan et al, 1977;Jweied et al, 2005). Thus, experimental findings in rodent models are likely to have utility in identifying underlying mechanisms of human diabetic cardiomyopathy.…”
mentioning
confidence: 62%
“…These findings were confirmed by Sharma et al, who demonstrated a fivefold to sixfold increase in intramyocardial lipid levels in obese, or type 2 diabetic, patients suffering from non-ischemic heart failure that was associated with a transcriptional profile similar to that of the Zucker diabetic fatty rat (Sharma et al, 2004). Finally, myofilament function is depressed in skinned fibers as a result of decreased Ca 2+ sensitivity, suggesting that Ca 2+ handling may also be impaired in human diabetic cardiomyopathy (Regan et al, 1977;Jweied et al, 2005). Thus, experimental findings in rodent models are likely to have utility in identifying underlying mechanisms of human diabetic cardiomyopathy.…”
mentioning
confidence: 62%
“…Myocytes were isolated from the interventricular septum and LV free wall of MICHF, POLVH, and age-matched control hearts by mechanical homogenization and chemically permeabilized (skinned) with 0.3% Triton X-100 (15,20). We observed no difference in myofilament function between septal and LV myocytes (data not shown).…”
Section: Methodsmentioning
confidence: 80%
“…However, whether depressed myofilament function contributes to reduced ventricular myocyte contractility in CHF is less clear (5). Studies probing myofilament activation in failing human myocardium must be interpreted with caution because tissue quality, pharmacological treatment, and brain death of donors may confound experimental findings (15,30,44). For these reasons, investigators have employed animal models that allow for the study of myofilament function under more carefully controlled circumstances.…”
mentioning
confidence: 99%
“…Animal studies show that there is increased post-translational modification of contractile proteins with phosphorylation of myofilament proteins troponin I and troponin T resulting in decreased Ca 2+ sensitivity (Akella et al, 1995). Myocardial tissue collected from diabetic and non-diabetic patients undergoing coronary artery bypass surgery showed that the presence of diabetes decreased Ca 2+ sensitivity (Jweied et al 2005). Diabetic patients also have a higher risk of developing hypertension than normoglycaemic individuals.…”
Section: Mechanisms Involved In Hyperglycaemia-aggravated Ischemic Hementioning
confidence: 99%